The Tryphosa group (Crustacea: Amphipoda: Lysianassoidea: Lysianassidae: Tryphosinae) - Kilgallen, N. M.; Lowry, J. K. (Zootaxa, 2014)
The Tryphosa group is established within the tryphosine amphipods. It contains eight genera worldwide (Bruunosa Barnard & Karaman, 1987; Glorieusella gen. nov.; Gronella Barnard & Karaman, 1991; Metambasia Stephensen, 1923; Pseudonesimus Chevreux, 1926; Schisturella Norman, 1900; Thrombasia J.L. Barnard, 1966; and Tryphosa Boeck, 1871). As part of the Tryphosa group we describe the new genus Glorieusella from Madagascar and four new species (Schisturella rosa sp. nov., Thrombasia evalina sp. nov., Thrombasia umina sp. nov., Thrombasia saros sp. nov.) from eastern Australia.